2009
DOI: 10.1016/j.febslet.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Pentagalloylglucose down‐regulates mast cell surface FcεRI expression in vitro and in vivo

Abstract: a b s t r a c tMast cell activation by immunoglobulin E (IgE)-mediated stimuli is a central event in the pathogenesis of allergic disorders. The present report shows that treatment with pentagalloylglucose (PGG) resulted in a down-regulation of FceRI surface expression on mucosal-type murine bone marrowderived mast cells (mBMMCs), which correlated with a reduction in IgE-mediated activation of mBMMCs. Furthermore, PGG prevented development of allergic diarrhea in a food-allergy mouse model and suppressed the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Previously, we have demonstrated that mucosal mast cells are primarily responsible for the pathology of FA in a murine FA model [6]. Connective tissue mast cell stabilizers (tranilast, ketotifen and cromolyn) and anti-histamine agents are frequently used to treat various allergic disorders other than FA, but these agents have no effect on mucosal mast cells [7]. Until now, little has been known about inhibitory agents against mucosal mast cell activation.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, we have demonstrated that mucosal mast cells are primarily responsible for the pathology of FA in a murine FA model [6]. Connective tissue mast cell stabilizers (tranilast, ketotifen and cromolyn) and anti-histamine agents are frequently used to treat various allergic disorders other than FA, but these agents have no effect on mucosal mast cells [7]. Until now, little has been known about inhibitory agents against mucosal mast cell activation.…”
Section: Introductionmentioning
confidence: 97%
“…However, later studies using human conjunctival mast cells additionally revealed a mast cell-stabilizing property of ketotifen [7,8], consistent with its higher potency in the treatment of allergic disorders. So far, by measuring the amount of chemokines released from rat peritoneal mast cells, such as histamine and β-hexosaminidase, previous studies have suggested the superiority of ketotifen to tranilast in the properties of mast cell stabilization [9][10][11]. However, due to the limitations of the methods used in molecular biology [12], the effects of these drugs on the exocytotic process of mast cells have not directly been examined.…”
Section: Introductionmentioning
confidence: 99%
“…14) FceRI, like a large number of cell surface receptors, is assumed to be dynamically transported within the cell. Rab5 has been shown to be a key regulator of various receptors transport in the early endocytic pathway.…”
Section: Discussionmentioning
confidence: 99%